2014
DOI: 10.1002/bip.22523
|View full text |Cite
|
Sign up to set email alerts
|

A combined small‐angle X‐ray and neutron scattering study of the structure of purified soluble gastrointestinal mucins

Abstract: The structures of purified soluble porcine gastric (Muc5ac) and duodenal (Muc2) mucin solutions at neutral and acidic pH were examined using small-angle X-ray scattering and small-angle neutron scattering experiments. We provide evidence for the morphology of the network above the semidilute overlap concentration and above the entanglement concentration. Furthermore, we investigated the gelation of both types of mucin solutions in response to a reduction in pH, where we observed the formation of large-scale he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 35 publications
7
27
0
Order By: Relevance
“…60,61 This fractal regime has been observed in a concentration range of 1.4 20 mg/mL. 61,62 At lower concentrations (0.3 mg/mL), the scattering curve (Figure 7a) allowed us to fit the Guinier function (log I(q) vs. q 2 , inset in Figure 7a) and to calculate a radius of gyration (Rg) of 18 ± 3 nm. The SAXS data suggest that our mucin preparation did not contain aggregates or highly-entangled insoluble fractions as indicated in previous studies 61 which would have increased the value of Rg.…”
Section: Polysaccharide Charge Is a Fundamental Component Of Interactmentioning
confidence: 81%
See 2 more Smart Citations
“…60,61 This fractal regime has been observed in a concentration range of 1.4 20 mg/mL. 61,62 At lower concentrations (0.3 mg/mL), the scattering curve (Figure 7a) allowed us to fit the Guinier function (log I(q) vs. q 2 , inset in Figure 7a) and to calculate a radius of gyration (Rg) of 18 ± 3 nm. The SAXS data suggest that our mucin preparation did not contain aggregates or highly-entangled insoluble fractions as indicated in previous studies 61 which would have increased the value of Rg.…”
Section: Polysaccharide Charge Is a Fundamental Component Of Interactmentioning
confidence: 81%
“…The detailed macromolecular structure of mucin has previously been investigated using highresolution scattering techniques, such as synchrotron SAXS, 60,61,62 SANS, 61,26,63 , static light scattering (SLS) and DLS 64 to compare the properties of mucin samples with different biological origins and preparation methods. The cylindrical model and the more recent double-globular comb model have therefore been used to account for the complex structure of mucin.…”
Section: Polysaccharide Charge Is a Fundamental Component Of Interactmentioning
confidence: 99%
See 1 more Smart Citation
“…When investigating relationships between physical properties and molecular structure, the determination of molecular organization within complex systems is fundamental; small-angle neutron scattering (SANS) -a powerful, non-destructive technique that probes organizational structure on a 1-200 nm lengthscale -can be easily applied for the study of delicate biological materials, although most studies published to date have focused on mucin [61][62][63][64][65].…”
Section: Small-angle Neutron Scattering Methodsmentioning
confidence: 99%
“…Georgiades et al [64] recently focused their studies on purified gastric and duodenal mucin using SANS and SAXS techniques. They confirmed that mucin forms a gel network above the semi-dilute concentration, studying the gel formation as a function of pH -a decrease in pH leads to microphse separation of the gels.…”
Section: Small-angle Neutron Scattering Methodsmentioning
confidence: 99%